MANAJEMEN BAITUL MAL PADA MASA KHALIFAH UMAR BIN KHATHAB R.A: SEBUAH TINJAUAN SEJARAH - Fitmawati Fitmawati (Institut Agama Islam Negeri Bengkulu, 2019)
Umar bin Khathab was the chaliph of about 10 years. He was well know as his ekspansion policies. He introduced a goverment administrasion system by dividing its area and building Baitul mal to be an independent institution. Those exspansion policies had reached the goal successfully, so as the income of the a sure of the Baitul mal were overabundance. Then, the chaliph Umar managed it through accumulation and emission by forming Diwan. He had applied the concept of Islamic management long before the weit management exisheted. The concent of Umar’s give preference on manner which related to the value of faith and truth. He also applied the Syura concept on manner and management activity, especially those which related to the determination of decision. Dividing goverment area and Amir and Madinah as the center of polity and Baitu mal the independent institution out of the goverment intervension became chaliph Umar contribution Islamic polity.